Development of an inhalable contrast agent targeting the respiratory tract mucus layer for pulmonary ultrasonic imaging - James K. Tsuruta; Patrick R. Sears; Meghan E. Rebuli; Andrew S. Weitz; Phillip G. Durham; Phillip W. Clapp; David B. Hill; Lawrence E. Ostrowski; Paul A. Dayton; Melissa C. Caughey (Scientific Reports)
Abstract Impaired mucociliary transport is a distinguishing sign of cystic fibrosis, but current methods of evaluation are invasive or expose young patients to ionizing radiation. Contrast-enhanced ultrasound imaging may provide a feasible alternative. We formulated a cationic microbubble ultrasound contrast agent, to optimize adhesion to the respiratory mucus layer when inhaled. Potential toxicity was evaluated in human bronchial epithelial cell (hBEC) cultures following a 24-hour exposure, compared to positive and negative control conditions. In vivo tolerability and pulmonary image enhancement feasibility were evaluated in mice, comparing oropharyngeal administration of contrast agent to saline control. When induced to flow across mucus plated on microscope slides, cationic microbubbles demonstrated greater affinity for target samples than standard microbubbles. Cationic microbubbles elicited no proinflammatory or cytotoxic response in hBECs, nor were any cross-links to the cilia observed. Unlike standard microbubbles, cationic microbubbles mixed into the mucus layer, without epithelial absorption, and were observed to move with the mucus layer by the action of mucociliary transport. When administered to mice, cationic microbubbles enhanced sonographic visualization of the trachea, and were well-tolerated with no adverse effects. This developmental work supports the safety and feasibility of a mucus-targeting contrast agent that may be useful for pulmonary ultrasound applications.